You’ve Got the Wrong Guy! I’m Innocent! Review of the Eleventh Circuit’s Holding in Sosa v. Martin County - Nathaniel Shulman (Washington University Journal of Law and Policy, 2025)
The Eleventh Circuit’s recent en banc decision in Sosa v. Martin County held that a person’s three-day detainment based on mistaken identity did not violate their substantive due process rights under the Fourteenth Amendment. Tracing the legal framework from the Supreme Court’s decision in Baker v. McCollan, this Note explains how courts have diverged in analyzing claims of wrongful detention based on mistaken identity. The Note argues that, while the Eleventh Circuit majority correctly applied precedent, the ruling showcases the flaws of a rigid three-day bright-line rule, which grants law enforcement broad discretion to detain individuals. Instead, the Note supports a Fourth Amendment approach that evaluates the reasonableness of prolonged wrongful detentions based on mistaken identity under a totality-of-the-circumstances standard. This approach better protects wrongful detainees from a legal deprivation of their constitutional rights while still accounting for law enforcement interests.
Keywords: DueProcessRights; WrongfulDetention; MistakenIdentity